E-Poster Viewings 2019
DOI: 10.1136/ijgc-2019-igcs.334
|View full text |Cite
|
Sign up to set email alerts
|

334 A prospective non-randomized study comparing the outcomes following complete versus selective parietal peritonectomy during CRS+HIPEC for advanced epithelial ovarian cancer

Abstract: Objectives To study the impact of the extent of CRS [complete Debulking (CD), optimal Debulking (OD)<1cm, or suboptimal Debulking (SOD) >1cm residual disease] on progression free (PFS) and overall survival (OS) in advanced EOC, PPC and FTC treated at AUBMC 1998-2018. Methods We retrospectively reviewed all patients with advanced disease who underwent either Primary debulking surgery (PDS) or if they had large tumor burden/multiple comorbidities/poor performance status, they received neoadjuvant chemotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Additionally, 60% of patients with advanced serous papillary peritoneal carcinoma treated with NACT followed by total parietal peritonectomy plus HIPEC showed microscopic disease when no disease was macroscopically evident at surgical exploration [29] . For advanced EOC in general, previous studies have reported 36% of patients with disease on pathological assessment with a normal looking visual assessment by surgeons [30] , whereas a high incidence of pathological residual disease has been observed even after a median of five cycles of neoadjuvant chemotherapy was used before interval debulking surgery [31] . In these settings, HIPEC also proved to have a role for EOC based on data of the OV-HIPEC trial by van Driel et al [4] , especially due to the higher risk of developing platinum resistance after NACT [32] .…”
Section: Clinical Commentarymentioning
confidence: 99%
“…Additionally, 60% of patients with advanced serous papillary peritoneal carcinoma treated with NACT followed by total parietal peritonectomy plus HIPEC showed microscopic disease when no disease was macroscopically evident at surgical exploration [29] . For advanced EOC in general, previous studies have reported 36% of patients with disease on pathological assessment with a normal looking visual assessment by surgeons [30] , whereas a high incidence of pathological residual disease has been observed even after a median of five cycles of neoadjuvant chemotherapy was used before interval debulking surgery [31] . In these settings, HIPEC also proved to have a role for EOC based on data of the OV-HIPEC trial by van Driel et al [4] , especially due to the higher risk of developing platinum resistance after NACT [32] .…”
Section: Clinical Commentarymentioning
confidence: 99%